Effect of time to operation on mortality for hypotensive patients with gunshot wounds to the torso: The golden 10 minutes. Issue 4 (October 2016) - Meizoso, Jonathan P.; Ray, Juliet J.; Karcutskie, Charles A.; Allen, Casey J.; Zakrison, Tanya L.; Pust, Gerd D.; Koru-Sengul, Tulay; Ginzburg, Enrique; Pizano, Louis R.; Schulman, Carl I.; Livingstone, Alan S.; Proctor, Kenneth G.; et al.
Abstract : INTRODUCTION: Timely hemorrhage control is paramount in trauma; however, a critical time interval from emergency department arrival to operation for hypotensive gunshot wound (GSW) victims is not established. We hypothesize that delaying surgery for more than 10 minutes from arrival increases all-cause mortality in hypotensive patients with GSW. METHODS: Data of adults (n = 309) with hypotension and GSW to the torso requiring immediate operation from January 2004 to September 2013 were retrospectively reviewed. Patients with resuscitative thoracotomies, traumatic brain injury, transfer from outside institutions, and operations occurring more than 1 hour after arrival were excluded. Survival analysis using multivariate Cox regression models was used for comparison. Hazard ratios (HRs) and 95% confidence intervals (CIs) are reported. Statistical significance was considered at p ⩽ 0.05. RESULTS: The study population was aged 32 ± 12 years, 92% were male, Injury Severity Score was 24 ± 15, systolic blood pressure was 81 ± 29 mm Hg, Glasgow Coma Scale score was 13 ± 4. Overall mortality was 27%. Mean time to operation was 19 ± 13 minutes. After controlling for organ injury, patients who arrived to the operating room after 10 minutes had a higher likelihood of mortality compared with those who arrived in 10 minutes or less (HR, 1.89; 95% CI, 1.10–3.26; p = 0.02); this was also true in the severely hypotensive patients with systolic blood pressure of 70 mm Hg or less (HR, 2.67; 95% CI, 0.97–7.34; p = 0.05). The time associated with a 50% cumulative mortality was 16 minutes. CONCLUSIONS: Delay to the operating room of more than 10 minutes increases the risk of mortality by almost threefold in hypotensive patients with GSW. Protocols should be designed to shorten time in the emergency department. Further prospective observational studies are required to validate these findings. LEVEL OF EVIDENCE: Therapeutic study, level IV.